Professional self-determination of students with SEN in the inclusive environment of higher school: problems, experience, prospects (Journal of Educational Sciences, 2023)
The article was written within the framework of the Project of the Ministry of Science and Higher Educationof the Republic of Kazakhstan IRN AR 14872130 “Formation of professional self-determinationof students with special educational needs (SEN) as a national strategy in the field of inclusive educationin the Republic of Kazakhstan” (2022-2024).The article raises the issues of creating an inclusive environmentin the higher education system of the Republic of Kazakhstan, which contributes to the professionalself-determination of students with special educational needs and their further successful employment.Based on the materials of the express survey, the experience of universities in creating conditions forstudents, allowing them to self-determine themselves in the conditions of higher education and acquirethe necessary social and labor skills, was analyzed.In particular, the results of an express survey of students with special educational needs demonstratedthe features and reasons for choosing a profession and further employment options, depending onpersonal and physiological characteristics, helped to clarify the gaps in creating an inclusive universityenvironment, to determine the prospects for further purposeful activities to form the readiness of thiscategory of students for successful professional self-determination.Key words: inclusion, inclusive education, persons with disabilities, students with special educationalneeds (SEN), professional self-determination.